Bridging Legends and Science: Field Evidence of a Large Tsunami that Affected the Kingdom of Tonga in the 15th Century - Lavigne, Franck; Morin, Julie; Wassmer, Patrick; Weller, Olivier; Kula, Taaniela; Maea, Ana V.; Kelfoun, Karim; Mokadem, Fatima; Paris, Raphael; Malawani, Mukhamad Ngainul; Faral, Audrey; Benbakkar, Mhammed; et al. (Frontiers in Earth Science, 2021)
The pre-colonial history (i.e. before the early 17th century) of Tonga and West Polynesia still suffers from major gaps because its reconstruction is essentially based on legends left by oral tradition, and by archaeological evidence somehow difficult to interpret. By the fourteenth century, the powerful Tu'i Tonga kingdom united the islands of the Tongan archipelago under a centralised authority and, according to tradition, extended its influence to neighbouring island groups in the Central Pacific. However, some periods of deep crisis were identified, e.g. in the mid- 15th century, marked by an abrupt cessation of inter-archipelago migration on the deep seas in the Pacific, significant cultural changes, and a decrease in accessible natural resources. The origins of these disturbances are still debated, and they are usually assigned to internal political problems or loss of external influence vis-à-vis neighboring states. However, the hypothesis of a major natural disaster was never suggested up to now, while field evidence points to the occurrence of a very large tsunami in the past, including the presence of numerous megablocks that were deposited by a "red wave" (or peau kula, which also mean tsunami in the Tongan language) according to a local myth. Drawing on a body of new evidence from sedimentary signatures and radiocarbon dating of charcoal and marine bioclasts, geomorphology, and sedimentology, in support of previously published archaeological data, we argue that a large tsunami inundated large areas of Tongatapu island in the mid-15th century with runup heights up to 30 m, and that the Tu’i Tonga kingdom was severely impacted by this event. We also discuss the likely sources of this tsunami, which happened in an isolated region of the world before the European maritime “great discoveries” early 17th century.